Comparison of three in vitro methods for determining and predicting the organic matter digestibility of complete diets for ruminants - Leeuw Klaas-Jan; Palić Dragan V. (Acta Periodica Technologica, 2009)
In this study, the organic matter digestibility (OMD) of six complete diets for ruminants has been determined in-vivo in trials with sheep and in-vitro using two-stage Tilley and Terry (T&T) method, gas production (GP) technique and multi-enzyme incubation (EDOM) procedures. The mean OMD values obtained in vivo and using T&T, GP and EDOM techniques were 684, 716, 685 and 710 g OM/kgDM respectively and did not differ significantly (P>0.05). The obtained in vitro results were regressed against determined in-vivo values to derive prediction equations. Using the T&T technique, the prediction equation OMD (in_vivo) = -17.36 + 0.98 x OMD (in_vitro_T&T), (R2 = 0.75; RMSE = 37.59) has been obtained. The equation OMD (in_vivo) = 198.98 + 0.71 x OMD (in_vitro_GP), (R2 = 0.21; RMSE = 66.36) has been derived for Gas production procedure, while the equation OMD (in_vivo) = 102 + 0.82 x OMD (in_vitro_EDOM), (R2 = 0.86; RMSE = 27.30) has been generated for multi-enzyme incubation technique. The results of this study showed that the OMD of complete diets for ruminants can be successfully determined, and in-vivo values predicted, using multi-enzyme incubation procedure, which is important because of the fact that rumen liquor, needed for the in-vitro twostage T&T and GP techniques is not always available to analytical laboratories.